An Empirical Study of Customer Satisfaction and Loyalty towards the CRM Practices adopted by different Banks - Singla, Ms. Jyoti; Bansal, Dr. Monica; Maan, Dr. Veerpaul Kaur (The journal of contemporary issues in business and government, 2021)
In India as well as world financial framework is the center of all monetary exercises including loans and investment, giving advances to foundations and private players for establishments. The present study investigates the impact of customer relationship management practices on the customer satisfaction in the banking sector. The study used survey design and the sample consisted of 780 respondents. These respondents were customers of different banks in the southern western region of Haryana. The results indicate that knowledge ability of employees and attitude towards clients is having significant influence on customer retention. Though, CRM practice of Efficiency of banking services was found to be insignificant. The study has managerial implications for the banking industry. The study also provides future guidelines.